Quarter car model stress analysis for terrain/road profile ratings. (4th October 2004) - Howe, J. Gavin; Chrstos, Jeffrey P.; Allen, R. Wade; Myers, Thomas T.; Lee, Dongchan; Liang, Chi-Ying; Gorsich, David; Reid, Alexander
The US Army currently uses the root mean square of elevation (RMSE) and power spectral density (PSD) to characterise road/terrain roughness for ground vehicle durability assessment. This paper describes research aimed toward improving these measures. One potential method is running a relatively simple, yet vehicle class specific model over a given terrain and using predicted vehicle response(s) to characterise the terrain. A precedent for this concept is the International Roughness Index (IRI), used in the highway industry. The IRI consists of a simple tyre model and quarter car vehicle model run at a specified speed to estimate suspension velocity over a road profile. Another method of estimating road roughness is fatigue analysis. In this study, a generic specimen was subjected to the quarter car suspension forces. The stresses developed were used to make a fatigue life cycle prediction. This paper presents the key concepts and results from this analysis.